IMPLEMENTATION OF GOOD CORPORATE GOVERNANCE TO SECURE ASSETS IN STATE-OWNED PALM OIL PLANTATION COMPANIES AND PRIVATELY-OWNED COMPANIES IN INDONESIA - Junaedy (Universal Journal, 2023)
Fact findings in the field regarding the Implementation of Good Corporate Governance to Secure Assets in State-Owned Palm Oil Plantation Companies and Privately-Owned Companies in Indonesia, especially Palm Oil Plantations which have State-owned status (Red Flat), all of this must be secured for continuity and sustainability. company business. Securing these assets must start from the smallest. An example in this research is the security of oil palm Fresh Fruit Bunches (FFB) which are often stolen, both by palm oil ninjas and palm oil mafias. Various modes of crime have emerged, such as theft of oil palm fresh fruit bunches, land use rights without rights and against the law, and other plantation crimes. This research is normative legal research that is descriptive analysis. The data used are secondary data and empirical data. Secondary data was collected using library study techniques and document study data collection tools. Meanwhile, secondary data was collected using field research techniques and data collection tools in the form of interviews using the in-depth interview method. Next, it is analyzed using qualitative analysis methods. The research results show that the implementation of Good Corporate Governance To Secure Assets In State-Owned Palm Oil Plantation Companies And Privately-Owned Companies In Indonesia is by the orders of the State-Owned Enterprises (BUMN) Law and BUMN Ministerial Regulation No. PER-01/MBU/2011 concerning the Implementation of Good Corporate Governance in BUMN; The application of GCG principles in an integrated security system has provided good results and there are obstacles to minimizing criminal acts of palm oil theft in state-owned and private companies, namely: there is the Republic of Indonesia Supreme Court Regulation No. 02 of 2012 concerning Adjustments to Limits for Minor Crimes which can exclude prosecution of perpetrators of theft whose evidence is less than Rp. 2.5 million; Palm oil theft is suspected to be carried out by unscrupulous company staff/employees who are dissatisfied with the company's welfare; and there is a structured and systematic legal culture of evil conspiracy between these elements. Thus, good corporate governance is needed in the field of asset security to minimize the theft of fresh palm oil fruit bunches in plantations. Assets In State-Owned Palm Oil Plantation Companies And Privately Owned Companies In Indonesia, which is called "Smart Security of Integrity ”.